IMPROVING TEACHING MATHEMATICS USING MODERN INFORMATION TECHNOLOGIES IN FORMATION MATHEMATICAL COMPETENCE REQUIRED FUTURE SKIPPERS. - Gudyreva О.М. (Journal of Information Technologies in Education (ITE), 2015)
The article is devoted to consideration of issues related to identifying the potential for teaching mathematics using network (Internet) technology and the introduction of elements of distance learning into educational process of higher educational establishments of the sea profile, as well as achievement of formation of mathematical competence of students of the University generally, and of the University’s Maritime profile, in particular. Based on the analysis of psychological and pedagogical literature highlights the factors that influence the increase of efficiency of independent work of students of higher educational institutions and on the formation of steady skills of self-education that ultimately leads to quality of formation of mathematical competence of a student. Specific features of teaching mathematics at the University of the sea profile. The description of the project (complex sites) "KSMA. Higher mathematics navigators",who developed and used in the Kherson state Maritime Academy in the teaching of mathematics and the organization of individual techniques of distance learning, shows the simplicity and accessibility of working with complex sites, as well as the simplicity and accessibility of design "personal website", but in fact complex sites, by a teacher of any discipline of higher education.Shown, also a training process with the use of the project "KSMA. Higher mathematics navigators", analyzes the experience of teaching the course "Higher mathematics" in a higher educational institution of the marine profile with the use of a personal website, a teacher and shown positive results in students mastery of basic mathematical competencies.